Description of the immatures of the predaceous midge Bezzia blantoni Spinelli & Wirth (Diptera: Ceratopogonidae) - Ronderos, Maria M.; Spinelli, Gustavo R. (Zootaxa, 2009)
The fourth instar larva and pupa of Bezzia blantoni Spinelli & Wirth (1989) are described, illustrated and photomicrographed by using phase-contrast microscopy and Scanning Electron Microscope (SEM). The larva, which shows features typical to carnivorous larvae, is compared with that of B. roldani Spinelli & Wirth. The species is recorded for the first time from the Martín García island, located in the La Plata river between Argentina and Uruguay. Details of the biology traits, breeding location and feeding behavior are given.